Design of a Flexible Exhibition Management Information System for Exhibition Services - Bin Hu (Hindawi Limited, 2021)
In order to solve the problems of low efficiency of management information systems and low utilization rate of the information resources, this research paper proposes the designs of an exhibition management information system by using a B/S structure (Browser/Server mode). The proposed system is aimed at the analysis of functions and types of exhibitions. The system is comprised of the following three components: the browser-side, server-side, and middle layer. Among them, the browser includes a user management module and exhibition environment visualization module. The server includes an upper computer control module and human-computer interaction module. The middle layer includes the data resource management module, document information management module, exhibition project audit approval and management module, and information scheduling module. Experimental results show that the lowest management efficiency of the system is 96.19%, the highest can reach 98.39%, and the utilization rate of information resources is above 94%, indicating that the system has achieved the design expectation.